EXHIBITION: Fair to cloudy? The Netherlands and Germany after 1945 on Display - Struver, Anke (Hagar: Studies in Society and Culture, 2002)
“Heiter bis wolkig” (“Fair to cloudy”) and ”Zimmer frei” (“Rooms to let”) are the titles of two exhibitions on Dutch-German relations. They were presented both in Germany (“Heiter bis wolkig,” Haus der Geschichte, Bonn: 22 Nov. 2000 - 16 Apr. 2001) and the Netherlands (”Zimmer frei,” Rijksmuseum, Amsterdam: 26 May - 16 Sep. 2001), focusing on the relations between the two countries after the Second World War.